Clonal selection in the human Vδ1 T cell repertoire indicates γδ TCR-dependent adaptive immune surveillance - Martin S. Davey (Nature Portfolio, 2017)
γδ T cells are generally considered innate‐like lymphocytes. Here the authors sequence human γδ T cell receptors (TCR) to show focusing of the private Vδ1 TCR repertoire, suggesting that, unlike Vδ2 T cells, the Vδ1 T cell compartment has adaptive attributes.